Análise comparativa das heurísticas de um software de roteirização por intermédio de parâmetros de produtividade: aplicação em uma empresa distribuidora de bebidas - Santos, Davidson de Almeida (2007)
The routing of vehicles in urban areas poses as a major problem in the area of logistics. This high level of complexity due to the multiplicity of restrictions to be considered for this kind of problem and the impact on costs generated at the time the routing of vehicles it is inefficient. This study develops a comparative analysis of the routing alternatives in a routing software of the company in a distributor of beverages. The study aims to contribute to analysis for better understanding of the problem of routing in urban areas and see where the scenarios routing alternative adapt itself better